The effect of mesenchymal stem cells combined with polycaprolactone/hydroxyapatite composite scaffold on the healing of ulnar defect in dogs - Sasijaras Tantrajak (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 2010